The role of mother-infant interaction and infant temperament in predicting the rate of post-NICU physical development in low birth weight infants: a prospective cohort study - Zijin Ren; Qihui Wang; Wenying Gao; Yi Duan; Yunling Li; Ying Zhang (BMC Pregnancy and Childbirth)
Abstract Background Low birth weight infants (LBWIs) discharged from NICU face significant growth retardation risks, however, their physical growth trajectories and the modifiable risk factors within mother-infant dyads remain insufficiently understood. This study aims to investigate how mother-infant interactions and infant temperament influence the rate of physical development in LBWIs. Methods A prospective longitudinal cohort of 273 LBWIs and their mothers was enrolled between September 2021 and March 2023. Primary variables included mother-infant interaction and infant temperament, while covariates encompassed socio-demographic and clinical data, and maternal postpartum depression. Latent growth curve models with time-varying covariates were employed to investigate the impact of mother-infant dyad-related factors on LBWIs’ physical growth. Results Higher mother-infant interaction quality at 1 month of corrected age (CA) (β=-0.190, P = 0.027) and 12 months CA (β=-0.228, P = 0.050) was associated with faster length and weight growth rate, respectively. In contrast, mother-infant interaction quality at 3 and 9 months CA was negatively correlated with LBWIs’ growth rate. Higher scores of temperament (surgency) at 3 months CA predicted faster weight growth rate (β = 0.217, P = 0.046). Conclusions The impact of mother-infant interaction on the growth rate of LBWIs varies at different time points, suggesting that tailored outpatient follow-up is crucial. Furthermore, infant temperament at 3 months CA positively influences the rate of development, indicating that interventions to nurture temperament may prove advantageous during this critical period. Therefore, mobile applications can be further developed to timely analyze interaction quality and guide parents through strategies that are best suited for their infant’s current developmental stage and temperament.